The Rationale for a Preventative HCV Virus-Like Particle (VLP) Vaccine - Torresi, Joseph (Frontiers in Microbiology, 2017)
HCV represents a global health problem with approximately 200 million individuals currently infected, worldwide. With the high cost of antiviral therapies, the global burden of chronic hepatitis C infection (CHCV) infection will be substantially reduced by the development of an effective vaccine for HCV. The field of HCV vaccines is generally divided into proponents of strategies to induce neutralizing antibodies (NAb) and those who propose to elicit cell mediated immunity (CMI). However, for a hepatitis C virus (HCV) vaccine to be effective in preventing infection, it must be capable of generating cross-reactive CD4+, CD8+ T cell and NAb responses that will cover the major viral genotypes. Simulation models of hepatitis C have predicted that a vaccine of even modest efficacy and coverage will significantly reduce the incidence of hepatitis C. A HCV virus like particle (VLP) based vaccine would fulfil the requirement of delivering critical conformational neutralizing epitopes in addition to providing HCV specific CD4+ and CD8+ epitopes. Several approaches have been reported including insect cell-derived genotype 1b HCV VLPs; a human liver-derived quadrivalent genotype 1a, 1b, 2 and 3a vaccine; a genotype 1a HCV E1 and E2 glycoprotein/MLV Gag pseudotype VLP vaccine; and chimeric HBs-HCV VLP vaccines. All to result in the production of cross-NAb and/or T cell responses against HCV. This paper summarizes the evidence supporting the development of a HCV VLP based vaccine.